Thy-1 Deficiency Augments Bone Loss in Obesity by Affecting Bone Formation and Resorption - Picke, Ann-Kristin; Campbell, Graeme M.; Schmidt, Felix N.; Busse, Björn; Rauner, Martina; Simon, Jan C.; Anderegg, Ulf; Hofbauer, Lorenz C.; Saalbach, Anja (Frontiers in Cell and Developmental Biology, 2018)
Healthy bone remodeling results from a balanced bone formation and bone resorption realized by bone-forming osteoblasts and bone-resorbing osteoclasts, respectively. Recently, Thy-1 (CD90) was identified as positive regulator of osteoblast differentiation and activation, thus, promoting bone formation while concurrently inhibiting adipogenesis and obesity in mice. Additionally, Thy-1 did not affect bone resorption. An obesity-related co-morbidity that is increasing in prevalence is a disturbed bone formation resulting in an increased fracture risk. The underlying mechanisms of obesity-induced bone alterations are not yet fully elucidated and therefore therapy options for efficient bone-anabolic treatments are limited. Therefore, we investigated the impact of Thy-1 on bone metabolism under obese conditions. Indeed, high fat diet (HFD) induced obese mice lacking Thy-1 (Thy-1−/−) showed increased body fat mass compared to wildtype (WT) mice while bone mass (−38%) and formation (−57%) were decreased as shown by micro-computed tomography (μCT) measurement, histological analysis, and fourier-transform infrared spectroscopy (FTIR). Interestingly, under obese conditions, lack of Thy-1 affected both osteoblast and osteoclast function. Number (−30%) and activity of osteoblasts were decreased in obese Thy-1−/− mice while osteoclast number (+39%) and activity were increased. Facilitated bone marrow fat accumulation (+56%) in obese Thy-1−/− mice compared to obese WT mice was associated with upregulated tumor necrosis factor α (Tnfα, +46%) and colony stimulating factor 1 receptor (Csf1r) expression, strong promoters of osteoclast differentiation. Moreover, lack of Thy-1 was accompanied by a reduction of osteoprotegerin (Tnfrsf11b) expression (−36%), an inhibitor of osteoclast differentiation. Altered Tnfα, Csf1r, and Tnfrsf11b expression might be responsible for elevated osteoclast activity in obese Thy-1-deficient mice. In summary, our findings show that lack of Thy-1 promotes obesity under HFD conditions while concurrently decreasing bone mass and formation. Mechanistic studies revealed that under obese conditions lack of Thy-1 impairs both bone formation and bone resorption.